Teaching economics in a changing South African environment - W. H. Thomas; Elti Links (South African Journal of Business Management, 1986)
This short, exploratory paper hopes to trigger further debate, research and other relevant action with regard to teaching economics in a changing South African environment. It is argued that the challenges confronting university teachers of under-graduate economics and the teaching of economics in secondary schools are many and diverse. Not least is the need to add to the teaching of general principles, the teaching of the actual functioning of the South African economy. The authors also consider curriculum development, teaching material, the training of teachers, university-technikon links and adult and non-formal education.
Keywords: 650